IMPLEMENTASI PEMIKIRAN FIQIH PRIORITAS YUSUF AL-QARDHAWI SEBAGAI UPAYA MEMBANGUN KEBIJAKAN BERBASIS KEMANUSIAAN - Ahmad Muhtadi Anshor; Muhammad Ngizzul Muttaqin (Fakultas Syariah (Syari'ah Faculty ), 2020)
As one group or individual who was given a special mandate by God to represent Him in the field of service to the interests of humanity, the government or the authorities certainly have a very heavy responsibility. On one side of God’s syari’ah and His provisions to create benefit for mankind and focus on the protection and special handling of the problems of the masses or problems of humanity. That is, the government as a representative of God, should have a policy that takes sides and prioritizes policies based on humanism. As a literature-based study and discussion of literature, this paper reveals a piece of ijtihad of a contemporary ulama’ Yusuf Qaradawi namely fiqh of priority. This study is very important for dissemination, looking at the problematics of government policy ideas that often override humanitarian problems, as well as the importance of using new analysis glasses in the form of studies based on Islamic law. So, this kind of study, can be used special considerations and add new treasures in contemporary Islamic legal thought.